2020
DOI: 10.3390/jcm9082400
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prevalence of Sensory Chemotherapy-Induced Peripheral Neuropathy for 5 Years after Adjuvant FOLFOX Chemotherapy to Treat Colorectal Cancer: A Multicenter Cross-Sectional Study

Abstract: (1) Background: Oxaliplatin is among the most neurotoxic anticancer drugs. Little data are available on the long-term prevalence and consequences of chemotherapy-induced peripheral neuropathy (CIPN), even though the third largest population of cancer survivors is made up of survivors of colorectal cancer. (2) Methods: A multicenter, cross-sectional study was conducted in 16 French centers to assess the prevalence of CIPN, as well as its consequences (neuropathic pain, anxiety, depression, and quality of life) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 51 publications
6
56
1
Order By: Relevance
“…Cold-induced neuropathy represents the most important difference between oxaliplatin and cisplatin-induced neuropathy [ 66 ] and its severity in the first phases of exposition has been associated to the chronic form of OIPN experienced one year later [ 67 ], observed in 50–70% of patients, depending on the intensity of symptoms assessed in its acute clinical presentation [ 68 , 69 , 70 ]. A systematic review by Beijers et al [ 71 ], in addition to the study by Briani et al has reported that OIPN may be present in 26–46% of patients at the 12-month follow-up, in 24% of patients at the 15–18-month follow-up and even in 84% of patients at the 24-month follow-up [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cold-induced neuropathy represents the most important difference between oxaliplatin and cisplatin-induced neuropathy [ 66 ] and its severity in the first phases of exposition has been associated to the chronic form of OIPN experienced one year later [ 67 ], observed in 50–70% of patients, depending on the intensity of symptoms assessed in its acute clinical presentation [ 68 , 69 , 70 ]. A systematic review by Beijers et al [ 71 ], in addition to the study by Briani et al has reported that OIPN may be present in 26–46% of patients at the 12-month follow-up, in 24% of patients at the 15–18-month follow-up and even in 84% of patients at the 24-month follow-up [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, recent in vivo and in vitro studies on CIPN states have yielded no major pharmacological advancements. Moreover, the majority of patients with CIPN receive no medical treatment for their symptoms [ 16 ]. These factors underscore the need for standardized, reliable treatments to improve cancer patients’ quality of life.…”
Section: The Burden Of Cipn and The Hope Of Flavonoidsmentioning
confidence: 99%
“…Oxaliplatin, paclitaxel, and bortezomib destabilize the nociceptor membrane by elevating the resting membrane potential toward the threshold; this increases the likelihood of an action potential. Oxaliplatin activates ion channels involved in action potential initiation and propagation [ 10 , 16 ]. Paclitaxel and bortezomib enhance the release of proinflammatory cytokines, which sensitize peripheral nociceptors [ 1 , 2 , 19 ] ( Figure 3 a).…”
Section: Flavonoids Counter the Effects Of Anticancer Drugs At Thementioning
confidence: 99%
See 1 more Smart Citation
“…However, alternatives to oxaliplatin should be sought, as there are severe and long-term neurotoxic AEs associated with this combination. 87 Artemisinin (malaria treatment) derivatives may be an alternative to oxaliplatin, as they are cytotoxic against colon cancer cells lines at low concentrations when used in combination with leucovorin and 5-fluorouracil (FOLNSC combination). 88 …”
Section: Introductionmentioning
confidence: 99%